Development of Community-Based Tourism Village through Local Community Participation (A Literature Review): Pengembangan Desa Wisata Berbasis Partisipasi Masyarakat Lokal (Sebuah Studi Literatur) - Fitra Riyanto; Awaludin Nugraha (Institute of Educational, Research, and Community Service, 2023)
Tourism development certainly involves the community, especially the development of tourist village tourism. The tourist village is one of the most developed tourism areas in Indonesia because it has the potential to support it. This study has the aim of knowing the development of tourist villages using the concept of community based tourism and the impact of implementing community based tourism for the community. The method used in this research is Literature Study. In this study, the development of a tourist village that uses the concept of community based tourism which involves the community of the tourist village area to manage the tourist village and the community has full involvement from the planning, implementation to evaluation stages as well as the impact on the community's economy with the tourism village which is getting better. This research is expected to be a consideration for the community to manage a tourist village.